2012
DOI: 10.1007/s00710-012-0195-9
|View full text |Cite
|
Sign up to set email alerts
|

On the presence of a hydrous component in a gemstone variety of intermediate olivine-type triphylite-lithiophilite, Li(Fe,Mn)PO4

Abstract: hydrous point defects in the structure of triphylite and/or sarcopside, which are possible under the assumption of vacancies at the Li (M1) and/or P sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Energy-dispersive system (EDS) elemental distribution maps reveal (b) depletion of P and (c) enrichment of Fe in a lamella compared to the host phase. Reprinted with permission from ref . Copyright 2012 Springer Verlag.…”
Section: Olivinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Energy-dispersive system (EDS) elemental distribution maps reveal (b) depletion of P and (c) enrichment of Fe in a lamella compared to the host phase. Reprinted with permission from ref . Copyright 2012 Springer Verlag.…”
Section: Olivinesmentioning
confidence: 99%
“…14 These minerals are formed in nature by hydrothermal reactions. Naturally occurring single crystals of Li[FeMn]PO 4 have been found to contain micron-size inclusions of sarcopside, as well as protons 15 as indicated in Figure 2. In 1981 Belov et al 16 reported the formation of LiFePO 4 under hydrothermal conditions close to the physicochemical conditions of phosphate mineral formation in nature, 400 °C and 968 atm for 100 h.…”
Section: Olivines 21 Occurrence and Synthesismentioning
confidence: 99%
“…The XO 4 3– → 4OH – substitution is well-known in the silicate minerals formed under hydrothermal conditions . This type of replacement gives rise to hydrogarnets (hydroxylated calcium aluminum silicates) , and humite-type defects in olivines n (Mg,Fe) 2 SiO 4 · m Mg 2 □ Si (OH) 4 (□vacancy). , On the basis of the IR spectra, the presence of a hydrous component in the natural triphylite was assumed to be partially associated with P vacancies . However, to our knowledge, the replacement of PO 4 3– by hydroxyl groups has never been considered in the context of defect chemistry of LiFePO 4 as the Li-ion battery cathode.…”
Section: Resultsmentioning
confidence: 91%
“…46,47 On the basis of the IR spectra, the presence of a hydrous component in the natural triphylite was assumed to be partially associated with P vacancies. 48 However, to our knowledge, the replacement of PO 4 3− by hydroxyl groups has never been considered in the context of defect chemistry of LiFePO 4 as the Li-ion battery cathode. Thus, we have performed density functional theory computations to estimate the energetics of the substituted phase, understand the location and bonding of protons and their influence on the crystal structure and Li diffusion barriers.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…On the basis of the IR spectra the presence of a hydrous component in the natural triphylite was assumed to be partially associated with P vacancies. 48 However, to our knowledge, the replacement of PO 4 3by hydroxyl groups has never been considered in the context of defect chemistry of LiFePO 4 as the Li-ion battery cathode. Thus we have performed density functional theory computations to estimate the energetics of the substituted phase, understand the location and bonding of protons and their influence on the crystal structure and Li diffusion barriers.…”
mentioning
confidence: 99%